An evaluation of the effects of the smoking ban at an acute NHS trust - Arack, R.; Blake, Holly; Lee, S.; Coulson, N. (Taylor & Francis, 2013)
The purpose of this study was to explore the effects of a complete smoking ban at an NHS Trust focusing on the attitudes, compliance and smoking behaviour of NHS Staff on the smoke-free NHS policy. Questionnaires were distributed to staff 17 months after the Trust implemented its smoking ban and two months before the nationwide smoking ban.